A systematic literature review of sustainability indicators in sustainability reporting. (16th January 2023) - Kumar, Manish; Joshi, Parikshit
In the past decade studies related to sustainability indicators (SIs), as a measure of sustainable development (SD), have steeply risen across several domains. Therefore, a systematic literature review (SLR) is required to assess the current state of studies on SIs. The current SLR identifies, evaluates, and synthesises the available literature on SIs published between 1994-2020 with an aim to explore the current development in the field and assess future research directions. The published literature from Web of Science and Scopus database was identified through automatic and manual search techniques and a total of 248 usable studies were finalised after inclusion-exclusion and quality assessment. Thematic analysis of the studies revealed that majority of the studies were from the theme - urban development area, followed by water resources and environment development, and the themes like social sustainability, social equity, dairy, green accounting and biotechnology are less explored.